I Can e l’ornitorinco. I generi musicali tra semantica lessicale e teoria pragmatica / Can and the platypus. Musical genres between semantic-lexical study and pragmatic theory - Marino, Gabriele (Rivista Italiana di Filosofia del Linguaggio)
The article aims at outlining a pragmatic model for the description of musical systems centred upon the notion of genre, meant as a set of both texts and properties mastered by a given individual, set within a given community, historically situated; the works of F. Fabbri served, in this respect, as a solid point of departure. The same musical text may trigger different features and properties for different individuals and communities, according to the degree and depth of their absolute and relative competences; with Gibson (and Eco), such features and properties may be called affordances, a good musical model of which may be Seeger/Tagg’s musemes (the musical equivalent to morphemes, basic musical units of meaning). Following the idea that musical genres’ names do nothing but crystallize possible or actual uses of the music (grounds, in Peircean-Echian terms), and that they propose them as model-uses to a model-listener, the author scrutinized circa 200 names of musical genres (mainly, ascribable to popular music), in order to find the dominant isotopies, namely the semantic recurrences, which identify the chief dimensions by which one can make sense of music. Six major macro-classes, or genre-definers, and as many possible valorizations, have been identified; musical genres’ names may talk about: the sonic or musical features themselves (e.g., industrial, drum’n’bass etc.); the function or the aim of the music (ambient, psychedelic); its lyrical content (love song, Christian metal); the implied socio-cultural context (gangsta, dark); its geographical origin (Latin jazz, Krautrock); a chosen, single element which has been assigned the role to synthesize the essence of the music (baggy, trap). The proposed model combines Lotman’s semiospheres and Rastier’s morphological semantics in the light of Xenakis’ music-as-clouds simile; a given musical text is understood as the entry of a blog, featured with a tag cloud (a set of tags; i.e., musical properties, affordances) and ascribed to one or more categories (genres).